Assessment of Compressive Strength of Concrete Using the CAPO Test - Khair, Abul (Journal of Engineering Science, 2024)
The CAPO-Test or the Cut and Pull-Out test, also known as the pull-out test, is gaining popularity as a method for estimating the compressive strength of existing concrete structures due to its reliability, less structural damage compared to core collection, and quick in-place strength. The manufacturer of the pull-out machine has provided a general correlation for assessing the in-place concrete strength of stone chip-based concrete. Many of the concrete buildings in Bangladesh are made of brick chip-based concrete. In a few projects in Bangladesh, the CAPO test has been used to assess the concrete strength of existing structures. However, the reliability of this test for concrete made of brick chips has yet to be investigated. 20 columns from five distinct structures, which varied in age from 14 to 45 years at the time of testing, underwent the CAPO and core tests for this study. Based on the fundamental findings of this investigation, a general correlation has been established regarding concrete composed of brick chips. According to the findings, the CAPO-Test f or concrete with brick chips shows estimated strengths using the proposed correlation varies between 0% and 30% of the core strength. No prior research has been identified on evaluating the concrete strength of existing structures containing brick chips using the CAPO test; therefore, this study supports the CAPO-Test's reliability in conducting in-situ concrete strength assessments of brick chip-based structures. Journal of Engineering Science 15(1), 2024, 1-10